Best practices for conceptual modelling in environmental planning and management. (June 2016) - Argent, Robert M.; Sojda, Richard S.; Guipponi, Carlo; McIntosh, Brian; Voinov, Alexey A.; Maier, Holger R.
Abstract: Conceptual modelling is used in many fields with a varying degree of formality. In environmental applications, conceptual models are used to express relationships, explore and test ideas, check inference and causality, identify knowledge and data gaps, synchronize mental models and build consensus, and to highlight key or dominant processes. Due to their sometimes apparent simplicity, development and use of a conceptual model is often an attractive option when tackling an environmental problem situation. However, we have experienced many examples where conceptual modelling has failed to effectively assist in the resolution of environmental problems. This paper explores development and application of conceptual modelling to environmental problems, and identifies a range of best practices for environmental scientists and managers that include considerations of stakeholder participation and trust, model development and representation, integration of different and disparate conceptual models, model maturation, testing, and transition to application within the problem situation. Highlights: Conceptual modelling is widely used in environmental management and planning. We have experienced many examples where conceptual modelling has failed. We identify eight elements of best practices for successful conceptual modelling.